A novel prime-&-rinse mode using MDP and MMPs inhibitors improves the dentin bond durability of self-etch adhesive. (April 2020) - Xu, Jingqiu; Li, Mingxing; Wang, Wenting; Wu, Zhifang; Wang, Chaoyang; Jin, Xiaoting; Zhang, Ling; Jiang, Wenxiang; Fu, Baiping
Abstract: Objectives: The study investigated the effects of novel prime-&-rinse mode using MDP (10-methacryloyloxydecyl dihydrogenphosphate) and matrix metalloproteinase (MMPs) inhibitors on dentin microtensile bond strengths (MTBS) of self-etch adhesive, resin-dentin interface degradations, and activity of recombinant human (rh) MMP-8, -9. Materials and methods: Eight experimental primers were prepared using 5% and 15% of MDP ethanol-aqueous (1:1) solution in combination with/without MMPs inhibitors (1%benzalkonium chloride (BAC), 1000 μm/mL polyvinylphosphonic acid (PVPA) and 15%proanthocyanidin (PA)). Ninety human mid-coronal dentin surfaces were applied with the experimental primers, water-sprayed and gently air-dried (prime-&-rinse mode), or not (control, self-etch mode). The specimens were bonded with self-etch adhesive (Clearfil S3 Bond) and composite resin (Clearfil Majesty). The resin-bonded specimens were prepared into multiple micro-beams for MTBS tests after 24 h and 1 yr of water storage. The resin-dentin interfaces were analyzed with SEM/TEM. The inhibitory effects of eight primers on rhMMP-8, 9 were determined. The data were analyzed using two-way ANOVA and LSD multiple comparisons tests. Results: Compared with control, all the primers used in prime-&-rinse mode could significantly improve long-term dentin MTBS ( P < 0.05), while 5%MDP-BAC, 15%MDP and 15%MDP+MMPs inhibitors could significantly increase the short-term dentin MTBS ( P < 0.05). The SEM/TEM findings revealed that the resin-dentin interfaces were stable over time when the prime-&-rinse mode used. Eight primers possessed the high inhibitory ratio of rh MMP-8, 9. Conclusions: The novel prime-&-rinse mode using 5%MDP-BAC, 15%MDP and 15%MDP+MMPs inhibitors could significantly increase the short- and long-term dentin MTBS of self-etch adhesive. This might be a supplement to contemporary dentin bonding strategies.